Sistem Pendukung Keputusan Siswa Terbaik Penerima Beasiswa Di SMP Putra Negara Jakarta Dengan Metode Analytical Hierarchy Process (AHP) Berbasis Java - Hafiidh Hafiidh; Muhammad Firdaus; Naely Farkhatin (JURNAL ILMIAH NUSANTARA, 2026)
The purpose of this research is to realize a SPK application with the Analytical Hierarchy Process (AHP) method which is useful for selecting Java-based scholarship recipients at SMP Putra Negara Jakarta accompanied by database processing built with MySQL. With the Analytical Hierarchy Process (AHP) method, it has been tested by SMP Putra Negara Jakarta and can run well so that the ranking of students to determine students to receive scholarships can be done as expected. If previously the selection took a longer time, now with the decision support system the selection time is shorte